2010
DOI: 10.1371/journal.pone.0011444
|View full text |Cite
|
Sign up to set email alerts
|

Case-Control Analysis of SNPs in GLUT4, RBP4 and STRA6: Association of SNPs in STRA6 with Type 2 Diabetes in a South Indian Population

Abstract: BackgroundThe inverse relationship between GLUT4 and RBP4 expression is known to play a role in the pathogenesis of type 2 diabetes. Elevated levels of RBP4 were shown to cause insulin resistance in muscles and liver. Identification of STRA6 as a cell surface receptor for RBP4 provides further link in this axis and hence we analyzed SNPs in these three genes for association with type 2 diabetes in a South Indian population.Methodology/Principal FindingsSelected SNPs in the three genes were analyzed in a total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
48
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 40 publications
1
48
3
Order By: Relevance
“…Two haplotypes (SNP (risk allele): rs3758538(A), rs3758539(G), rs10882283(G), c248C44TOC(T), rs12265684(G), rs10882273(C); and rs3758539(G), 390COG(G), 406TOC(T), rs36014035(G), rs12265684(G), rs34571439(T), rs12766992(G), rs10882273(C)) are significantly increased in Caucasians with T2D when compared with healthy controls (33,48). Four SNPs in Mongolian population (SNP (risk allele): rs3758539(A), rs7094671(T), rs12265684(C), and 7542TOdel(del)) and a haplotype in South Indian population (rs3758538(C), rs3758539(T), rs36014035(G), and rs34571439(T)) have also been determined that are associated with T2D (31,49). Haplotype (SNP (risk allele)) rs3758538(A), rs3758539(G), rs10882283(G), c248C44TOC(T), rs12265684(G), rs10882273(C)) is also associated with higher mean fasting plasma insulin and 2 h plasma glucose in OGTT in non-diabetic Caucasians (33).…”
Section: Rbp4 In Insulin Resistance and T2d: Clinical Studiesmentioning
confidence: 99%
“…Two haplotypes (SNP (risk allele): rs3758538(A), rs3758539(G), rs10882283(G), c248C44TOC(T), rs12265684(G), rs10882273(C); and rs3758539(G), 390COG(G), 406TOC(T), rs36014035(G), rs12265684(G), rs34571439(T), rs12766992(G), rs10882273(C)) are significantly increased in Caucasians with T2D when compared with healthy controls (33,48). Four SNPs in Mongolian population (SNP (risk allele): rs3758539(A), rs7094671(T), rs12265684(C), and 7542TOdel(del)) and a haplotype in South Indian population (rs3758538(C), rs3758539(T), rs36014035(G), and rs34571439(T)) have also been determined that are associated with T2D (31,49). Haplotype (SNP (risk allele)) rs3758538(A), rs3758539(G), rs10882283(G), c248C44TOC(T), rs12265684(G), rs10882273(C)) is also associated with higher mean fasting plasma insulin and 2 h plasma glucose in OGTT in non-diabetic Caucasians (33).…”
Section: Rbp4 In Insulin Resistance and T2d: Clinical Studiesmentioning
confidence: 99%
“…However, till date, no information is available on the expression of STRA6 (RBP4 receptor) under these conditions. In a recent study, a G[A single-nucleotide polymorphism in STRA6 was found to be significantly associated with elevated risk of development of T2D in a South Indian cohort (27). This mutation is predicted to alter the trafficking and cell surface expression of this protein, thus suggesting a critical role of STRA6 in the development of insulin resistance.…”
Section: Plasma Rbp4 Ttr and Retinol Levels In Type 2 Diabetesmentioning
confidence: 99%
“…Recently, two independent studies in south Indian population revealed that SNP haplotypes of GLUT4 gene marginally associate with T2D [12,13]. Therefore, in this study, we retrieved two SNPs, rs5418 and rs2654185, from the south Indian studies and determined their association with T2D prospective trait of HbA1c in a Japanese population.…”
mentioning
confidence: 99%